The right price : a value-based prescription for drug costs - Neumann, Peter J., 1961-; Cohen, Joshua T.; Ollendorf, Daniel A. (New York, NY : Oxford University Press, 2021)
The pharmaceutical industry and its pricing methods provide an inviting target, easy to disparage and caricature. Even after accounting for discounts and rebates, average prices of leading brand-name drugs in the US are two to four times higher than they are in Canada, Japan, and many European countries. US per capita spending on prescription drugs is more than twice the level in the United Kingdom. Prices for most new cancer drugs now exceed $100,000 per patient per year of treatment, despite the fact that many of these treatments seem to offer modest gains in life expectancy or lack such evidence at all. With the advent of ever more targeted and powerful treatments, including cell- and gene-based therapies with multi-million dollar price tags, the need for sensible drug pricing and coverage policies will intensify.
The prescription drug market -- Proposed solutions for rising drug prices -- Measuring the value of prescription drugs -- Measuring drug value : whose job is it anyway? -- Institute for Clinical and Economic Review (ICER) -- Other US value assessment frameworks -- Do drugs for special populations warrant higher prices? -- Improving value measurement -- Aligning prices with value -- The path forward.
Includes bibliographical references and index.
Keywords: Prescription Fees; Drug Costs